Sosialisasi Miskonsepsi Pembelajaran IPA pada Guru MGMP IPA KKM MTs. Kecamatan Batukliang - Mulia Rasyidi; Muh. Zaini Hasanul Muttaqin; Asrorul Azizi; Fena Prayunisa (Jurnal Inovasi dan Pengabdian kepada Masyarakat (JIPMas), 2026)
Misconceptions in Science learning constitute a persistent problem that can hinder students’ conceptual understanding, particularly when such misconceptions are held by teachers. This community service activity aimed to improve the conceptual understanding of Madrasah Tsanawiyah Science teachers regarding learning misconceptions as well as strategies for their prevention and remediation. The activity was conducted through socialization sessions, group discussions, case study analyses, and training on the development of diagnostic assessments involving Science teachers from the Subject Teacher Forum of the Madrasah Working Group in Batukliang District. Data were collected using pre- and post-activity understanding questionnaires, observations, and participant reflections, and were analyzed descriptively. The questionnaire results indicated an increase in the teachers’ average understanding score from 57.6 before the activity to 81.8 after the activity. Improvements were also observed in teachers’ abilities to identify student misconceptions and to design diagnostic assessments. It was concluded that the activity was effective in strengthening teachers’ conceptual competence and contributed to improving the quality of Science learning in Madrasah Tsanawiyah.